Pathological Complete Response in Locally Advanced Breast Cancer after Neoadjuvant Chemotherapy: Survival Outcome and Its Relevance as a Surrogate End Point - Reshu Agarwal; U. G. Unnikrishnan; Pavithran Keechilat; Anupama Rajanbabu; Wesley Jose; D. K. Vijaykumar (South Asian Journal of Cancer, 2020)
Background Pathological complete response (pCR) to neoadjuvant chemotherapy has emerged as a reliable surrogate marker for improved survival in breast cancer (BC), but its role as a surrogate end point is still controversial. Aims and Objectives The aim of the study is to investigate the clinical course of BC patients with pCR and to evaluate the relevance of pCR as a surrogate end point for survival. Materials and Methods This was a single-institution retrospective analysis done at Amrita Institute of Medical Sciences. Records of BC patients from 2004 to 2014 were analyzed. Disease-free survival (DFS) and overall survival (OS) were compared using the Kaplan–Meier method and log-rank test, respectively. pCR and survival association were evaluated using regression analysis (R 2). Results Of 224 patients included in the study pCR rate was 15.2%. The median duration of follow-up was 61 months (range: 3–151 months). DFS (73.4 vs. 46.1%, p = 0.032) and OS (82.5 vs. 56.4%, p = 0.022) of pCR cohort was significantly higher than non-pCR cohort. Recurrence rate was significantly lower in the pCR cohort at: All distant sites (p = 0.01 3), visceral sites (p = 0.007), both bone and visceral sites (p = 0.007), and nodal sites (p = 0.007). There was no difference in the bone-only recurrence (p = 0.3 15). Death rate was significantly lower in pCR cohort (p = 0.007). The R2 value for pCR as a surrogate for DFS and OS was 0.006 and 0.004, respectively. Conclusion pCR is a favorable prognostic factor associated with improved survival. However, there is no association between pCR and survival.